ANALYSIS OF THE INFLUENCE OF HUMAN RESOURCE COMPETENCE AND SERVICE QUALITY ON CUSTOMER SATISFACTION OF THE REGIONAL SECRETARIAT OF SURABAYA CITY - Warih Anggraini; Dewie Tri Wijayanti; Andre Dwijanto Witjaksono (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The purpose of this study is to determine the influence of human resource competence and service quality on customer satisfaction of the Surabaya City Regional Secretariat. This research is a quantitative descriptive research. Data collection was carried out through the distribution of questionnaires with a research sample of 122 respondents from a population of 176 respondents. The statistical analysis used in this study is Multiple linear regression with the help of Software SPSS. Data testing instruments are carried out by data validity tests, data reliability tests and The classical assumption test consists of a normality test, a multicollinearity test, an autocorrelation test, and a heterokedasticity test. The method used to test the hypothesis is to use the Partial Influence Test (t- Test), the Simultaneous Influence Test (Test F) and the Determination Test (R2). The results of the study show that there is an influence of human resource competence, tangibles, reliability, responsiveness, assurance, and Empathy have a positive and significant effect both partially and simultaneously on customer satisfaction of the Derah Secretariat of the City of Surabaya.